Depiction of Vayu - Temples of India Project Team (Jio Institute, 2024)
Vayu is depicted standing with a gentle smile. His four arms bear testament to his celestial nature. In his upper hands, he grasps a staff, symbolizing authority and guidance. His lower hands cradle a kamandalu (water pot) and extend in varadaksha (boon-giving gesture with a rosary). At the base, his vahana (mount), the antelope, is depicted in graceful motion, adding to the dynamic energy of the scene.